Assessing Indonesia's Peatland Management Strategies Under the ASEAN Transboundary Haze Pollution Second Road Map - Tjahjadi, Bryan Gadrian; Teeja, Nathania Wiandra; Tjahjadi, Patrick James (Faculty of Law, Universitas Pelita Harapan | Lippo Village, Tangerang 15811 - Indonesia, 2024)
Peatland ecosystems in Southeast Asia are vital carbon sinks and biodiversity reserves, yet they face persistent threats from unsustainable land-use practices, particularly fire-based land clearing. Indonesia, which holds a significant share of the region’s tropical peatlands, remains a key actor in addressing the environmental and transboundary haze crises stemming from peatland degradation. As a member of ASEAN, Indonesia is bound by regional commitments, including the ASEAN Agreement on Transboundary Haze Pollution and the ASEAN Second Haze-Free Roadmap (2023–2030), which promotes sustainable peatland management through strategies such as the ASEAN Peatland Management Strategy (APMS). This paper aims to critically assess Indonesia’s peatland management strategies in light of these regional obligations. It evaluates the implementation and enforcement of the Zero Burn Policy, the current state of peatland rehabilitation and preservation efforts, the institutional and legal roles of the Indonesian government, and comparative insights drawn from other ASEAN member states. This research uses a combination normative and empirical juridical research methodology, integrating doctrinal legal analysis with contextual evaluation of implementation practices. Despite regulatory advancements and institutional initiatives, Indonesia continues to face significant challenges, including weak enforcement, persistent land burning, and fragmented governance. The paper concludes that achieving sustainable peatland management and fulfilling ASEAN commitments requires stronger inter-agency coordination, enhanced legal clarity, and deeper regional collaboration rooted in shared environmental governance principles.